2022
DOI: 10.1002/npr2.12293
|View full text |Cite
|
Sign up to set email alerts
|

Development of individual fitness score for conformity of prescriptions to the “Guidelines For Pharmacological Therapy of Schizophrenia”

Abstract: Clinical practice guidelines are developed to standardize and improve the quality of medical care, and several guidelines for schizophrenia have been published. [1][2][3][4] In Japan, the "Guidelines for Pharmacological Therapy of Schizophrenia" by the Japanese Society of Neuropsychopharmacology has been published. 1 However, it is unclear to what extent the guidelines are followed in clinical settings. Thus, we launched the "Effectiveness of Guidelines for Dissemination and Education in Psychiatric Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…A low QI score does not necessarily indicate a clinical problem, and it is considered necessary to establish appropriate target values for each QI. We also recently developed an individual fitness score formula that expresses the degree to which prescribers adhere to the guidelines for schizophrenia and major depressive disorder 46,47 . An individual fitness score could be useful to visualize the degree to which current prescriptions conform to the guidelines for each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low QI score does not necessarily indicate a clinical problem, and it is considered necessary to establish appropriate target values for each QI. We also recently developed an individual fitness score formula that expresses the degree to which prescribers adhere to the guidelines for schizophrenia and major depressive disorder 46,47 . An individual fitness score could be useful to visualize the degree to which current prescriptions conform to the guidelines for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…We also recently developed an individual fitness score formula that expresses the degree to which prescribers adhere to the guidelines for schizophrenia and major depressive disorder. 46,47 An individual fitness score could be useful to visualize the degree to which current prescriptions conform to the guidelines for each patient. However, there is an important limitation.…”
Section: Pcn Psychiatry Andmentioning
confidence: 99%
“…In Japan, the Effectiveness of Guidelines for Dissemination and Education (EGUIDE) psychiatric treatment project, which aims to disseminate the guidelines that present the treatments for schizophrenia and major depressive disorder via education programs for psychiatrists, was reported to be effective 25–27 . In addition, to easily visualize the degree to which current prescriptions conform to the guidelines for the pharmacological treatment of schizophrenia, 24 the individual fitness score (IFS) is an effective tool, in which points vary in range from 0 to 100 28 . To prevent severe complications due to antipsychotic‐induced constipation, careful monitoring is needed for patients treated with high‐risk antipsychotics for constipation such as levomepromazine maleate, olanzapine, quetiapine, zotepine and clozapine.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 , 27 In addition, to easily visualize the degree to which current prescriptions conform to the guidelines for the pharmacological treatment of schizophrenia, 24 the individual fitness score (IFS) is an effective tool, in which points vary in range from 0 to 100. 28 To prevent severe complications due to antipsychotic‐induced constipation, careful monitoring is needed for patients treated with high‐risk antipsychotics for constipation such as levomepromazine maleate, olanzapine, quetiapine, zotepine and clozapine. In cases of severe constipation, decreasing the dose of antipsychotics or switching to low‐risk antipsychotics should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, we should assess several QIs according to multiple guideline recommendations; thus, a single indicator summarizing multiple QIs (with values ranging from 0 to 100 points) can facilitate evaluation of adherence to guideline recommendations. Recently, we developed an individual fitness score (IFS) in each patient to evaluate whether pharmacological treatments (prescriptions) in each clinician adhere to the Guidelines for Pharmacological Therapy of Schizophrenia (see Table 1 in the paper by Inada et al, 2022 ) and confirmed the validity of the IFS using a survey of the prescriptions at admission and discharge among EGUIDE project participants ( Inada et al, 2022 ). However, a combined evaluation of clinician adherence and patient outcomes is needed.…”
Section: Introductionmentioning
confidence: 93%